Implementation of Murabahah Agreement on Peer to Peer Lending Platform - Muhammad Irkham Firdaus; Haerul Akmal; Setiawan bin Lahuri (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2022)
ABSTRACTPeer to Peer Lending is the best solution for MSME entrepreneurs, so the development of start-up is very fast. Ease in the mechanism offered is a major factor in accelerating the growth of the start-up. So that, it makes to began for developing several Peer to Peer Lending platforms in Indonesia. But, the system used is still based on the conventional economic system, which still takes advantage of the interest system while interest is strictly prohibited in Islam. Interest in Islamic Economics is analogous as usury. Whereas in fiqh muamalah, lawful transactions are transactions that are independent of the maghrib elements (maisyir, gharar, and usur). So that, the Peer to Peer Lending transaction is independent of the maghrib elements, the researcher will create a Peer to Peer Lending design that is in accordance with Islamic economic principles, by implementing the murabahah contract on the Peer to Peer Lending transaction. So, the benefits taken do not use the usury system.